Feasibility and reproducibility of substituting oral contrast with water for duodenal volume delineation in patients undergoing pancreatic stereotactic body radiotherapy - Wu, Guangyin; Häfner, Matthias (Journal of gastrointestinal oncology, 2017)
Background: This is the first known report evaluating the feasibility of substituting oral contrast with water in efforts to delineate the duodenum for pancreatic stereotactic body radiotherapy (SBRT). Methods: From January 2015 to August 2016, 13 patients were simulated after ingestion of 8 ounces of water approximately 15-20 min prior to their simulation scan. We examined the feasibility of contouring the duodenum thereafter, and measured the duodenal volume as well as its variation. Comparison was made to 40 patients treated from January 2009 to February 2012 on a prospective trial who used oral contrast. Group comparisons were performed by the Mann-Whitney U test. Results: The duodenum was identified in all 13 patients who used water instead of oral contrast without subjective difficulty. In this group, the median duodenal volume was 72.86 cm 3 (range, 44.61-130.90 cm 3 ). In the oral contrast group, median duodenal volume was 86.21 cm 3 (range, 50.11-157.89 cm 3 ) There were no significant differences between groups (P=0.115). The approach was reproducible, as all patients were able to drink the same amount of water 15-20 min prior to each SBRT fraction to keep duodenal volumes subjectively similar to volumes on the simulation CT scan. Conclusions: This novel approach is effective and reproducible in delineating the duodenum for treatment planning and daily setup.